PTU-086 Suboptimal Performance of Shearwave Elastography (ElastPQ) for Predicting Advanced Fibrosis in a Nafld Enriched Cohort. (17th August 2016) - Bevan, R; Stenberg, B; Madhra, M; McNeill, A; McPherson, S
Abstract : Introduction: It is important to identify those at risk of advanced liver fibrosis in order to stratify care. Histological assessment by liver biopsy (LBx) is the gold standard for staging liver fibrosis, but is impractical for widespread use. Several non-invasive measures of fibrosis, such as transient elastography and simple markers (FIB4 score and AST/ALT ratio (AAR)) have shown promise as alternatives to LBx. Shearwave elastography (SWE), assessed using acoustic radiation force impulses (ARFI), offers a potential alternative technique that can be performed on a conventional ultrasound machine. To date, few studies have evaluated the Phillips ElastPQ system, particularly in patients with non-alcoholic fatty liver disease (NAFLD). Our aim was to evaluate the accuracy of SWE using ElastPQ compared with liver biopsy in a "real world" cohort. Methods: Patients undergoing LBx between Sept 2014-Dec 2015 who had SWE conducted at the time of LBx were included. Clinical and demographic data were collected from the time of LBx. The AAR and FIB4 scores were calculated. Liver fibrosis was staged from 0–4; stage 3–4 was considered advanced fibrosis. SWE was conducted by experienced sonographers. SWE values (m/s) were defined as normal (<1.21), fibrotic (1.21–1.55) or advanced fibrosis/cirrhotic (>1.55). Results: 92 patients were identified (52% male; median age 51 yrs, range 20–90). LBx diagnoses were: 57 NAFLD, 10 AIH, 9 PBC, 6 HBV/HCV and 10 other. Median biopsy size was 20 mm (IQR 16.2–24). Overall, there was significant correlation between SWE and fibrosis stage (r = 0.44 p <0.001) and the FIB4 score (r = 0.32 p =0.004). Table 1 shows a Cross-tabulation of SWE fibrosis categories against fibrosis stage. Patients who were correctly classified with SWE are shown in bold. Worryingly, 6 patients (24%) with advanced fibrosis had a "normal" SWE reading. For all patients, the area under the receiver operator curve (AUROC) for a diagnosis of advanced fibrosis was 0.73 for SWE (sensitivity[sen] 46%, specificity[sp] 78% at 1.55 m/s), 0.81 for the FIB4 score (sen 85%, sp 65% at 1.3) and 0.8 for the AAR (sen 76%, sp 73% at 0.8). When the 57 NAFLD patients were analysed separately the AUROCs for advanced fibrosis were 0.72, 0.84 and 0.83 for SWE, FIB4 and AAR respectively. Conclusion: In this real world cohort, SWE using ElastPq had suboptimal performance and missed clinically significant advanced fibrosis in 24% of cases. It appears that this technique does not perform as well in patients with NAFLD as other liver diseases, such as viral hepatitis. Disclosure of Interest: None Declared